Experts' tools, altruists, and job-seekers: visions of community health workers in Ethiopia's antiretroviral centre of excellence. Issue 3 (1st September 2016) - Maes, Kenneth
Abstract : This article reports on research conducted during 2007–2008 within an antiretroviral therapy (ART) programme in Addis Ababa, run as a partnership between NGOs, government health officials, and international donors. Through examination of the discourses of professionals in NGO and government sectors, and of the community health workers (CHWs) who delivered ART support and home-based care, I show how a policy of volunteerism worked on the ground, through complex interactions that generated targeted success: thousands of new patients getting on and adhering to free ART, and living longer. CHWs were variously treated by these other actors as human resources to be managed, as heroic and altruistic volunteers, and as potentially self-interested. CHWs behaved as altruistic and self-sacrificing volunteers, yet also attempted to assert – individually and collectively – their desires to gain employment in order to better themselves and their communities. Much of the growing body of research on CHWs studies down, adopting a human resources mentality and collecting data from CHWs, to help identify policies by which health systems might more cost-effectively use CHWs in the production of better population health. Rather than a critique of this mentality, the research presented here represents a shift to studying both up and down structures of CHW programme implementation and governance, to help understand the varied ways in which CHW programmes in Africa today work, and how CHWs' interests and power over their job conditions and social policies will evolve.